Comparison of echocardiography and chest X-ray for initial diagnosis of heart failure: bibliographic review - Miranda, Dario Javier Caguate; Torres, Anahí Alejandra Cárdenas (International Journal of Research in Medical Sciences, 2025)
Heart failure is a common pathology that continues to be one of the leading causes of cardiovascular death worldwide. Timely and accurate detection is essential to provide adequate treatment and improve the patient’s clinical evolution. This review seeks to analyze the initial diagnostic potential of heart failure between transthoracic echocardiography versus chest X-ray, two tools commonly used in medical practice. For this purpose, studies published between 2000 and 2024 were reviewed, taking sensitivity, specificity, strengths and weaknesses of each diagnostic study as main indicators. The results indicate that transthoracic echocardiography offers a sensitivity between 80-95% and a specificity between 85-98%, whereas chest X-ray presents lower sensitivity data with 59-79% and a specificity close to 96%. Although transthoracic echocardiography proves to be more accurate for confirming the diagnosis of heart failure, chest X-ray retains its utility as an initial evaluation method due to its accessibility, speed, and low cost.